Phytoseiid mites on grasses in Brazil (Acari: Phytoseiidae) - Lofego, Antonio C.; Demite, Peterson R.; Kishimoto, Raquel G.; de Moraes, Gilberto J. (Zootaxa, 2009)
Surveys were conduced in 16 sites in the State of São Paulo to evaluate the phytoseid mite fauna on some of the most common grass species in that State: Brachiaria decumbens Stapf., Brachiaria brizantha (Hochst. ex A. Rich.) Stapf, Brachiaria ruziziensis R. Germ & C.V. Evrard, Melinis minutiflora Beauv., Panicum maximum Jacq. and Pennisetum purpureum Schumach. Twenty known species and one new species (Proprioseiopsis biologicus Lofego, Demite & Moraes sp. nov.) were found. Two species are reported for the first time in the American continent: Neoseiulus benjamini Schicha and Typhlodromus (Anthoseius) neobakeri Prasad . Seven of the species collected have been reported in Brazil from different crops. The largest number of specimens and of species of phytoseiids was found on M. minutiflora. The results of this study indicate that grasses may play a role in agroecosystems and pasture lands, serving as reservoirs of phytoseiids that prey upon mite pests.